Проблема охлаждения расплава кориума в контейнменте в пассивных системах защиты от тяжелых аварий. Часть 1 - Калванд, Али; Казачков, И.В. (Ядерна та радіаційна безпека, 2009)
В реакторах третьего поколения наличие пассивных систем защиты от тяжелых
аварий — обязательное требование, поэтому работа имеет важное значение для
ядерной безопасности. Рассмотрено несколько таких систем, находящихся в разной
степени завершенности, дан анализ теплогидравлических проблем и методы их решения
для усовершенствования существующих систем или создания новых, более эффективных.
Разработанные математические модели и проведенный анализ могут быть полезными
при конструировании пассивных систем удержания расплава кориума в контейнменте
после его выхода из разрушенного корпуса реактора. У реакторах третього покоління наявність пасивних систем захисту від тяжких
аварій — обов'язкова вимога, тому робота мае важливе значения для ядерної безпеки.
Розглянуто декілька таких систем, що знаходяться в різних фазах завершеності, надано
аналіз теплогідравлічних проблем іметоди їхнього розв'язання для вдосконалення існуючих
систем або створення нових, більш ефективних. Розроблені математичні моделі та
проведений аналіз можуть бути корисними при конструюванні пасивних систем
утримання розплава коріуму в контейнменті після його виходу з реактора. This paper is devoted to an analysis of the problem of corium melt interaction with water and lowmelting
temperature blocks in the passive protection systems against severe accidents a t the NPP, which
is of high importance for substantiation of the nuclear power safety, for building and successful operating
of the passive protection systems. In the third-generation reactors the passive protection systems against
severe accidents at the NPP are mandatory, therefore this paper is of importance for the nuclear power
safety. A few such systems have been considered, which are in different stage of completeness. An
analysis of the unsolved thermal hydraulic problems, which solution might help to improvement of the
current systems or development of the new, more effective ones has been provided. The ways for solution
of the stated problems and the methods for their successful elaboration were discussed. The mathematical
models developed and the analysis performed in the paper might be helpful for design of the passive
systems of the corium melt retention inside the containment after a corium melt eruption from the failed
reactor vessel.